Developing Actor-Based Middleware as Collector System for Sensor Data in Internet of Things (IoT) - Trisnawan, Primantara Hari; Bakhtiar, Fariz Andri; Pramukantoro, Eko Sakti (Journal of Information Technology and Computer Science, 2020)
The use of Internet of Things (IoT) plays an important role in supporting wireless communication for middleware in collecting data sensors. An actor-based middleware is designed to bridge protocol differences between cloud and sensor nodes. This middleware also acts as an initiator in accessing data from several sensor nodes, and then sending data that has been collected to the cloud. Incorporating the differences of communication protocols and data formats between sensor nodes and cloud is the responsibility of middleware. This Middleware acts as an actor by acting proactively accessing data from each sensor node, so that it can facilitate the completion of sending data from the sensor node to the middleware by avoiding from "signal collisionsâ€ among sensor nodes. After the data is collected in the middleware, the data is sent to the cloud using the Websocket or HTTP protocol above the TCP / IP protocol. The performance of the system is evaluated based on the success of the middleware bridging communication between sensor nodes and the cloud, as well as the readability of IoT data sensors that have been adjusted by cloud. The test results show that built-in middleware can bridge protocols between cloud and sensor nodes. In addition, the Websocket usage protocol produces a lower delay value than the MQTT and CoAP protocols.